Pengaruh Metode Latihan Running With The Ball terhadap Hasil Kecepatan Dribbling pada Tim Sepak Bola Putri Cahaya Gunung Kabupaten Kendal - Astuti, Eni Budi; Sudarmono, Martin (Indonesian Journal for Physical Education and Sport, 2023)
The speed of football players is also useful for running speed, changing direction and speed in shooting and kicking the ball. The purpose of this study was to determine the effect of running with the ball exercise on the results of dribbling speed on Cahaya Gunung female team Kendal Regency. This research is a quantitative research with the one group post test and pre test design research design. The object of this research is 16 players. The data analysis technique used the t test with a significant level of 5% or 0.05. The results of the t test on the hypothesis obtained the value of t count 8.938 > t table 2.074, the results concluded that there was an effect of the running with the ball training method on the results of dribbling speed on Cahaya Gunung female team Kendal Regency. The results of the percentage increase in dribbling speed obtained by running with the ball exercise had an increase of 27.01%. The conclusions in this study, there is an effect of running with the ball exercise on the results of dribbling speed on Cahaya Gunung female team Kendal Regency. The advice that researchers can give is that it is hoped that coaches and players can implement running exercises with the ball so as to increase dribbling speed